‘TranSonic’ Perception in Interactive ChoreoSonic Performance Practice - Zofia Sleziak (Body, Space & Technology Journal, 2011)
This paper reflects on the creation and perception of an interactive spatial ChoreoSonic performance environment. The term ‘Transonic Perception’ is introduced to describe the intimate bodily experience of the dancer who creates the 3D spatial sonic environment within the technologically enhanced environment. I will discuss conceptual issues that outline a synchronicity between the spatial elements of dance movement and 3D spatial sound perception that can be used artistically in the creative process. The discussion focuses specifically on the human perception of the visual, tactical and auditory space in the digitally enhanced performance environment.